Analysis Of Project Scheduling Using The CPM Method (Case Study Of Prayer Room Construction In PT. X Empalecement Complex) - Try Sugiyarto Soeparyanto; Ridwasyah Nuhun; Annisa; Yusran; Hendra Ariatno; La Ode Muh. Zulfitrah (Journal of Civil Engineering and Planning (JCEP), 2024)
In a construction project work, it is necessary to control time, quality and costs. This control is necessary to obtain work results that are in accordance with planning. The aim of this research is to determine the results of the analysis of the application of the Critical Path Method (CPM) to time scheduling on the prayer room construction project at the PT emplacement complex. X. The results of this research show that with the CPM method, the project completion time is determined within 26 weeks. Critical incidents obtained include preparation work (A), earth work (B), concrete work (C), roof and ceiling work (E), electrical work (H), painting work (I), and site cleaning (J). . The critical path consists of two paths, namely 1-2-3-4-6-9-10-11 and 1-2-3-4-5-8-9-10-11.